'It's changed how we have these conversations': emergency department clinicians' experiences implementing firearms and other lethal suicide methods counseling for caregivers of adolescents. (3rd October 2021) - Salhi, C.; Berrigan, J.; Azrael, D.; Beatriz, E.; Barber, C.; Runyan, C.; Miller, M.
Abstract: Counseling parents to reduce access to firearms and other potentially lethal suicide methods is commonly known as lethal means counseling (LMC). The current study explores the experiences that emergency department-based behavioural health clinicians described having as they provided lethal means counseling to parents of adolescents at risk for suicide. Clinicians were purposively sampled from four hospital networks in Colorado after their hospitals adopted LMC protocols as part of an intervention that also included online training in LMC and provision of free medication and firearm lockboxes. Twenty-three clinicians were interviewed using semi-structured interviews. Data were analysed using a modified grounded theory-based approach. Clinicians felt more comfortable and effective in their abilities to provide LMC after the intervention. Clinicians also described how being able to offer free storage devices helped them engage in LMC. In advising parents to make guns and medications inaccessible to their at-risk child, most clinicians pointed to at least one of three research findings highlighted in the online training: (1) Suicide attempts with guns rarely afford second chances, (2) medication overdoses can kill, (3) suicidal behaviour is always unpredictable and often impulsive. All clinicians described a desire to continue LMC as currently protocolized at their hospital after the study ended.